Le jardin des supplices - Mirbeau, Octave, 1848-1917 (Salt Lake City, UT : Project Gutenberg, 2018)
"Le jardin des supplices" by Octave Mirbeau is a novel published in 1899. This provocative work follows a French political operative sent on a dubious mission to Ceylon, where he encounters the enigmatic Clara, an English woman who guides him through a Chinese torture garden. Through disturbing descriptions and dark humor, the novel explores violence, colonialism, and what Mirbeau calls the universal "law of murder" that underlies all societies. Its deliberately ambiguous tone challenges readers to question civilization, morality, and the boundaries between beauty and horror. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Torture_Garden Wikipedia page about this book: https://fr.wikipedia.org/wiki/Le_Jardin_des_supplices
Release date is 2018-08-26
Keywords: Torture -- Fiction; French fiction -- 19th century